Artretyzm : jak leczyc go dieta - Scala, James, 1934-; Gasparska, Grazyna (Warszawa : Ksiazka i Wiedza, 2000)
Polish translation of "New arthritis relief diet". A guide to treating arthritis throught proper diet.
Translation of: The new arthritis relief diet.
Keywords: Arthritis -- Diet therapy